Is there a Business Cycle Component in Norwegian Macroeconomic Quarterly Time Series? - Terje Skjerpen (Statistics Norway, Research Department, 1995)
Some main Norwegian quarterly macroeconomic time series are decomposed into unobserved components within the framework of structural time series models using UCARIMA models. In the most general case we allow for a stationary cyclical component besides a stochastic trend, a stochastic seasonal and an irregular component. The cyclical component is either interpreted as a part of the trend component or as a component which is additive to the trend. For some of the investigated time series it is possible to extract business cycle component, but the the parameters characterizing it are not very presicely estimated and besides the component itself does not seem to be important.
Keywords: C22; C51; E32; 330; Business cycles; UCARIMA